Real-World Data on Antibiotic Group Treatment in European Livestock: Drivers, Conditions, and Alternatives - Julia Jerab; Wiebke Jansen; John Blackwell; Jobke van Hout; Andreas Palzer; Stephen Lister; Ilias Chantziaras; Jeroen Dewulf; Nancy De Briyne (MDPI AG, 2022)
Major efforts have been made by veterinary professionals to reduce the need for antibiotic use in animals. An online survey launched by the Federation of Veterinarians of Europe (FVE) aimed to gather responses from practicing veterinarians with field experience in metaphylactic livestock group treatment. Only 17% of all veterinarians (n = 183/1087, all species-specific responses merged) applied metaphylactic group treatments to 75% or more of all their treatments. Significantly less metaphylactic group treatments were reported in mixed practices (p = 0.002) and practices specialized in cattle (p < 0.001) as well as small (p = 0.007) and very small practices (p = 0.009). Gram-negative bacteria, mostly composed of Enterobacteriaceae and Pasteurellaceae, were considered by 75.3% (n = 967/1385) as the most devastating bacterial pathogens. Respondents alleged morbidity (20.1%, n = 201/998) and mortality (42.2%, n = 421/998) as major consequences for animal health and welfare if metaphylaxis would be banned. Responding veterinarians pointed towards vaccinations; improved biosecurity, including hygiene measures; and improved herd health management as the three most effective alternative measures to prevent metaphylactic treatment. However, more research is needed on how to implement appropriate alternatives in a holistic hurdle approach. Active support on a national level will be necessary for the development and application of targeted veterinary treatment guidelines for practitioners, which promote the understanding of drivers and include initiation criteria for metaphylactic group treatments in livestock.